Taming the Sculptress: Roman Beauty and Marble Love in Alcott’s Art Tales - Daniela Daniele (European Journal of American Studies)
In her feminization of Hawthorne’s famous Italian tales, Alcott made of her talented heroines not only objects but subjects of their art. The excellent training of many of her aspiring women sculptors follows the Oedipal patterns which oppressively dominate Nathaniel Hawthorne’s own Roman artworld. Being victimized by a Puritan ideal of beauty that no living body could equal, Alcott’s feminized versions of The Marble Faun allude to the American colony of women sculptors led by the actress Charlotte Cushman, whose extraordinary accomplishments in the arts challenged the patriarchal demands of the male gaze.